2019
DOI: 10.4081/jphia.2019.1212
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of speech delay and family factors

Abstract: Speech delay is one common developmental disorders in children. The purpose of this study was to detect factors that affect speech delay in children aged 48- 72 months. This quantitative research used analytical design with cross sectional approach. 159 children were chosen as samples in this study. Data analysis used chi square test. The results showed that family factors of speech delay with p value of 0.853 and factor of working mothers with p value 0.245. In this study, it can be concluded that there is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
(11 reference statements)
0
3
0
2
Order By: Relevance
“…Penggunaan kosa kata dan kecakapan anak dalam berbahasa bergantung pada pengalaman yang didapatkan anak di dalam keluarga dan lingkungan (Kurniasari & Sunarti, 2019). Keluarga khususnya orang tua memegang peranan yang sangat besar dalam membantu perkembangan berbicara dan bahasa anak yakni melalui cerita, tebak-tebakan, permainan kata, bernyanyi, membaca buku bersama (McLaughlin, 2011).…”
Section: Pendahuluanunclassified
“…Penggunaan kosa kata dan kecakapan anak dalam berbahasa bergantung pada pengalaman yang didapatkan anak di dalam keluarga dan lingkungan (Kurniasari & Sunarti, 2019). Keluarga khususnya orang tua memegang peranan yang sangat besar dalam membantu perkembangan berbicara dan bahasa anak yakni melalui cerita, tebak-tebakan, permainan kata, bernyanyi, membaca buku bersama (McLaughlin, 2011).…”
Section: Pendahuluanunclassified
“…14 One study, on 159 children of ages between 48-72 months, from Indonesia found that there is no relationship of delayed speech in children with working status of mothers. 15 A previous study reported an incidence of delayed language and speech in Thai children as 11.9%. 16 One more study from Saudi Arabia described prevalence of language and speech delay was 24.5%.…”
Section: Discussionmentioning
confidence: 96%
“…This is like the results of a journal review from Istiqlal (2021) that teachers provide a stimulus to speak to children who have speech delay disorders with more portions than other friends. Kurniasari & Sunarti (2019) stated that language stimulation is an activity to stimulate children's language so that children have optimal development. Every child needs to get regular stimulation as early as possible and continuously and this can be done by mothers, fathers, caregivers, and their closest relatives.…”
Section: Teacher's Role In Handling Early Childhood Speech Delaymentioning
confidence: 99%